Differences in LC3B expression and prognostic implications in oropharyngeal and oral cavity squamous cell carcinoma patients - Kenneth Lai; Slade Matthews; James S. Wilmott; Murray C. Killingsworth; Jim L. Yong; Nicole J. Caixeiro; James Wykes; Allan Samakeh; Dion Forstner; Mark Lee; John McGuinness; Navin Niles; et al. (BMC Cancer, 2018)
Abstract Background This study examined the prognostic significance of microtubule-associated protein light chain 3B (LC3B) expression in oropharyngeal and oral cavity squamous cell carcinoma (SCC). The prognostic significance of LC3B expression in relation to human papillomavirus (HPV) status in oropharyngeal SCC was also examined. Methods Tissue microarrays (TMAs) were constructed from formalin-fixed, paraffin-embedded oropharyngeal (n = 47) and oral cavity (n = 95) SCC tissue blocks from patients with long-term recurrence and overall survival data (median = 47 months). LC3B expression on tumour was assessed by immunohistochemistry and evaluated for associations with clinicopathological variables. LC3B expression was stratified into high and low expression cohorts using ROC curves with Manhattan distance minimisation, followed by Kaplan–Meier and multivariable survival analyses. Interaction terms between HPV status and LC3B expression in oropharyngeal SCC patients were also examined by joint-effects and stratified analyses. Results Kaplan–Meier survival and univariate analyses revealed that high LC3B expression was correlated with poor overall survival in oropharyngeal SCC patients (p = 0.007 and HR = 3.18, 95% CI 1.31–7.71, p = 0.01 respectively). High LC3B expression was also an independent prognostic factor for poor overall survival in oropharyngeal SCC patients (HR = 4.02, 95% CI 1.38–11.47, p = 0.011). In contrast, in oral cavity SCC, only disease-free survival remained statistically significant after univariate analysis (HR = 2.36, 95% CI 1.19–4.67, p = 0.014), although Kaplan-Meier survival analysis showed that high LC3B expression correlated with poor overall and disease-free survival (p = 0.046 and 0.011 respectively). Furthermore, oropharyngeal SCC patients with HPV-negative/high LC3B expression were correlated with poor overall survival in both joint-effects and stratified presentations (p = 0.024 and 0.032 respectively). Conclusions High LC3B expression correlates with poor prognosis in oropharyngeal and oral cavity SCC, which highlights the importance of autophagy in these malignancies. High LC3B expression appears to be an independent prognostic marker for oropharyngeal SCC but not for oral cavity SCC patients. The difference in the prognostic significance of LC3B between oropharyngeal and oral cavity SCCs further supports the biological differences between these malignancies. The possibility that oropharyngeal SCC patients with negative HPV status and high LC3B expression were at particular risk of a poor outcome warrants further investigation in prospective studies with larger numbers.